Design, optimization, and validation of a magnetic mother-child robot system for targeted drug delivery - Bentao Zou; Huibin Liu; Xuehao Fen; Zhizheng Gao; Zhixing Ge; Wenguang Yang (Materials & Design)
Traditional untethered magnetic microrobots utilized for in vivo targeted drug delivery face challenges related to poor maneuverability and limited kinematic performance. In this study, we harness the strengths of both magnetic continuum robots (acting as “mother” units) and untethered microrobots (functioning as “child” units), refining the motion model to develop a magnetically driven mother–child robotic system. We have also enhanced the structural design of the magnetic continuum and optimized the batch fabrication process of pH-responsive hydrogel integrated with the microrobots. This design allows the child robots to be deployed by the mother unit and subsequently retrieved upon task completion. Our strategy, which aims to minimize foreign body presence and reduce side effects, was validated using an in vitro gastric model, demonstrating the feasibility and enhanced operability of this system.